Participation of Students With Disabilities in Higher Education: Policy and Practices Melissa Ng Lee Yen Abdullah, School of Educational Studies, - Abdullah, Melissa Ng Lee Yen; Tan, Clarene (National Higher Education Research Institute, Universiti Sains Malaysia, 2016)
Equity, in general refers to fairness or justice. The promotion of equity through policies and practices requires the individuals’ or groups’ needs and circumstances to be taken into account (Matear, 2006). Access to higher education should not be taken out of the context of equity (Asian Development Bank, 2012). Policy on equitable access, therefore, seeks to provide students with disabilities with greater opportunities to access tertiary education, which is driven by a sense of justice and fairness. Students with disabilities are still underrepresented in higher education at most countries, particularly in developing countries. Based on the policy and practices in developed countries, this paper aims to reflect on the provision of equitable higher education for students with disabilities at a selected developing country.